2022
DOI: 10.1111/eea.13186
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic potential of Bacillus subtilis and Bacillus amyloliquefaciens strains against Musca domestica under controlled conditions

Abstract: The housefly, Musca domestica L. (Diptera: Muscidae), is a key pest in animal production areas; the resistance of this insect to chemical insecticides makes it necessary to develop new control alternatives. The aim of this work was to study the entomopathogenic activity of eight strains of Bacillus subtilis Ehrenberg ssp. subtilis and two strains of Bacillus amyloliquefaciens Priest et al., isolated from different ecological niches, against the housefly. Cell suspension (CS) of each Bacillus strain and cell‐fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The bacteria B. amyloliquefaciens has insecticidal activity against Myzus persicae and an inhibitory effect on the ability of insects to reproduce due to its active enzymes and live cells that have the ability to kill insect pests [30]. Also, B. amyloliquefaciens showed reduced survival of Musca homestica [31]. [32] reported that oxymatrine and azadirachtin provide effective control against Tetranychus evansi on tomato; oxymatrine treatments caused higher mortality (60-88%) and reduced its fertility (73.1-90.7%), where oxymatrine controlled the immature individuals and adult females of T. evansi faster than azadirachtin; also, oxymatrine-based treatments were highly efficient on newly hatched T. evansi larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria B. amyloliquefaciens has insecticidal activity against Myzus persicae and an inhibitory effect on the ability of insects to reproduce due to its active enzymes and live cells that have the ability to kill insect pests [30]. Also, B. amyloliquefaciens showed reduced survival of Musca homestica [31]. [32] reported that oxymatrine and azadirachtin provide effective control against Tetranychus evansi on tomato; oxymatrine treatments caused higher mortality (60-88%) and reduced its fertility (73.1-90.7%), where oxymatrine controlled the immature individuals and adult females of T. evansi faster than azadirachtin; also, oxymatrine-based treatments were highly efficient on newly hatched T. evansi larvae.…”
Section: Discussionmentioning
confidence: 99%